OPTIMIZING HEAT TRANSFER IN INNOVATIVE SOLAR WATER HEATERS USING RECYCLED MATERIALS: ENHANCING EFFICIENCY AND SUSTAINABILITY - Ekram Alaskaree (Mağallaẗ Al-kūfaẗ Al-handasiyyaẗ, 2025)
The study demonstrates the efficiency of using recycled materials to create solar water heaters, in particular in enhancing heat transfer. The innovative heater surpasses traditional commercial models in performance, offering a sustainable solution for residential water heating. The research, conducted in Baghdad, Iraq, entailed reusing heat exchangers from an outdated air conditioner to serve as a solar water heater collector. Equipped with a thermal insulator ,and an electronic control system, the heater achieved impressive results, raising the water temperature to 55 o C in just 30 minutes with a thermal efficiency of 83.122%. While the commercial heater took an hour and a half to heat the water to 57 o C. By integrating features such as serpentine fins, black coating and foam insulation, the system increases heat absorption and reduces losses. The electronic control system enhances the efficiency of heat transfer, which makes the homemade solar heater a viable and affordable option whose manufacture costs no more than 30,000 IQD while the commercial one costs 179,000 IQD. Both are environmentally friendly for residential use. In general, the research emphasizes the possibility of using recycled materials to develop efficient and sustainable solar water heating systems.